Residents’ perception towards social and cultural impacts on hosting a sports’ event / Radzliyana Radzuwan, Nadiah Diyana Tan Abdullah and Nasyitah Tp Harun - Radzuwan, Radzliyana; Tan Abdullah, Nadiah Diyana; Tp Harun, Nasyitah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Today sport and tourism are among the developed worlds’ most sought-after leisure experiences and are becoming very important reflecting the host venue both socially and culturally. In this new era, many challenges were even more significant for Malaysia as she is not yet developed like other countries. Therefore, a careful selection of a potential place as a host venue for sports’ event is important. In line with that notion, this study aims to examine residents’ perception towards social and cultural impacts on hosting World Kite Festival in Pasir Gudang, Johor. A self-administered questionnaire was developed. A total of 461 residents were successfully surveyed and their perceptions towards social and cultural impacts were assessed by utilizing Scale of Perceived Social Impact (SPSI). All obtained data were further analyzed by using Statistical Package for Social Science (SPSS). In order to achieve the research objectives, descriptive statistic was used for assessing the percentages, mean, rank and standard deviation. While independent t-Test was used to investigate the gender differences among residents at World Kite Festival. The finding indicates that there was a positive impact of hosting a sports’ event to the resident at Pasir Gudang although some negative impacts were witnessed. Thus, some improvement is needed.